Respuesta :

Gyzmo

Answer:

The answer is -6.

Step-by-step explanation:

To find the value of y in (3, y), plug in 3 for x in y = -(2x) and solve for y.

y = -(2(3))

y = -6

y = -6, so the answer is -6.

Answer:

-8

Step-by-step explanation:

I think the equation you want is y=-(2^x) because if you meant what you put originally the first guy is right.

What you do is take 2^3 which equals 8 and then you have the negative left which gets you to -8. I probably explained this terribly and I am sorry.

ACCESS MORE